AN ERROR ANALYSIS OF THE WRITTEN PRODUCTION BY THE SECOND GRADE STUDENTS OF SMA MUHAMMADIYAH 1 SURAKARTA, ACADEMIC YEAR 2005/2006 - NAGARI , HENDRARINI BUDI (2007)
This research is aimed at describing the errors of sentence, finding the most dominant errors, and classifying the sources of the errors of errors. In collecting the data, the writer uses elicitation method. She asks the students to produce the language through written form. Then, the writer classifies the errors based on surface strategy taxonomy. Based on the result of the data analysis, the writer finds 4 types of errors. There are 9 omissions in the form of: (1) -s/-es in the verb of present tense, (2) "to be" as a verb in the present tense, (3) subject in the present tense, (4) verb in the present tense, (5) article, (6) preposition, (7) -s in the subject plural form, (8) infinitive marker "to", (9) "to be" in the progressive tense, and the total of omission is 107 / 45,53%. There are 4 additions in the form of: (1) -ed in the verb of simple past tense, (2) "to be" in the present tense, (3) unnecessary article, (4) unnecessary preposition "to", and the total of addition is 69 / 29,36%. There are 6 misformation in the form of: (1) misused of object instead of subject, (2) misused of object pronoun instead of possessive adjective, (3) misused of subject pronoun instead of object pronoun, (4) inappropriate vocabulary, (5) using "have" instead of "has", (6) misused of "to be", and the total of misformation is 29 / 12,34%. There are 2 misordering in the form of: (1) word order, (2) false concept sentences, and the total of misordering is 32 / 12,76%. From the result of analysis it can be found that the dominant type of error is Omission with the total number of errors 107 or 45,53 %. Besides, there are two sources of error namely Interlingual transfer and Intralingual transfer. The result of this study is that most of the students still make errors in expressing their ideas. Therefore, there is necessity of Remedial teaching.